"A Noble Dream" renewed: reflections on the origins of Library and Archives Canada. Issue 1 (1st December 2022) - Wilson, Ian E.
Abstract : In May 2004, the Government of Canada amalgamated the National Library (established 1953) and the National Archives (established 1872) to form Library and Archives Canada. The unusual Preamble to the legislation provided the new institution with an ambitious mandate, summoning the values and commitment of librarians, archivists and the many professions required in a modern knowledge institution. This article reflects on the origins of the Canadian approach to archival service and the historical context of the new institution. This combined approach is not meant as a model for other nations as it was shaped by local circumstance. In the absence of both a national library and museum until the mid-twentieth century, the national archives took a holistic approach selecting and preserving official and private archives but also collecting and exhibiting historical evidence in the form of pamphlets, posters and newspapers, documentary art and portraits, a variety of artifacts and in due course, film. Its public outreach initially focused on assisting the emerging historical profession but has increasingly balanced this with initiatives to serve all interested Canadians. When the National Library was formed in 1953, its acquisition mandate was strictly limited to publications by Canadians or about the country, a mandate which harmonized with the archives. Both institutions shared a building and common administrative support services. The rapid digitization of both recordkeeping and publishing combined with social media, the Internet and growing public expectation for convenient access provided the catalyst for creating a new knowledge institution to serve Canadians in the twenty-first century.